UNDERSTANDING THE URBAN POPULATION DENSITY AND GROWTH CONCENTRATION IN PALEMBANG INDONESIA - Muhammad Fajri Romdhoni (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2020)
ABSTRACT This research is to understand the current condition of Density, population, and growth concentration in the city of Palembang. As one of the oldest cities in Indonesia, Palembang has been one of the twelve fastest growing cities in Indonesia, with more than one point six million people in 2018. According to the 2018 United Nations booklet (Nations, 2018) the Indonesian cities will grow with the annual rate of 2.4% to 6%, and undoubtedly this growth will impact the city’s urban fabric. This paper uses the Landsat images, and OpenStreetMap (OSM) data sets combined from the 2018 Population statistics in Palembang by overlaying the data to examine the statistical growth and urban density in the city of Palembang. The maps will also use the space syntax method and natural street analysis to determine the human behavior and traffic movement pattern and how the current urban layout should be examined. This street network's potential will serve as a narrative for further development to the city of Palembang. Keywords: density, population growth, natural street, space syntax, Palembang.